BTEX biodegradation by bacteria from effluents of petroleum refinery - Christofoletti Mazzeo, Dania Elisa [UNESP]; Levy, Carlos Emilio; de Angelis, Dejanira de Franceschi [UNESP]; Mann-Morales, Maria Aparecida [UNESP] (Elsevier B.V., 2010)
Groundwater contamination with benzene, toluene, ethylbenzene and xylene (BTEX) has been increasing, thus requiring an urgent development of methodologies that are able to remove or minimize the damages these compounds can cause to the environment. The biodegradation process using microorganisms has been regarded as an efficient technology to treat places contaminated with hydrocarbons, since they are able to biotransform and/or biodegrade target pollutants. To prove the efficiency of this process, besides chemical analysis, the use of biological assessments has been indicated. This work identified and selected BTEX-biodegrading microorganisms present in effluents from petroleum refinery, and evaluated the efficiency of microorganism biodegradation process for reducing genotoxic and mutagenic BTEX damage through two test-systems: Allium cepa and hepatoma tissue culture (HTC) cells. Five different non-biodegraded BTEX concentrations were evaluated in relation to biodegraded concentrations. The biodegradation process was performed in a BOO Trak Apparatus (HACH) for 20 days, using microorganisms pre-selected through enrichment. Although the biodegradation usually occurs by a consortium of different microorganisms, the consortium in this study was composed exclusively of five bacteria species and the bacteria Pseudomonas putida was held responsible for the BTEX biodegradation. The chemical analyses showed that BTEX was reduced in the biodegraded concentrations. The results obtained with genotoxicity assays, carried out with both A. cepa and HTC cells, showed that the biodegradation process was able to decrease the genotoxic damages of BTEX. By mutagenic tests, we observed a decrease in damage only to the A. cepa organism. Although no decrease in mutagenicity was observed for HTC cells, no increase of this effect after the biodegradation process was observed either. The application of pre-selected bacteria in biodegradation processes can represent a reliable and effective tool in the treatment of water contaminated with BTEX mixture. Therefore, the raw petroleum refinery effluent might be a source of hydrocarbon-biodegrading microorganisms. (c) 2010 Elsevier B.A. All rights reserved.
Keywords: BTEX; Genotoxicity; Mutagenicity; Allium cepa; HTC cells; Pseudomonas putida